A 90-nm CMOS Low-Power GSM - Lueftner, T.
To meet the widely varying speed and power requirements of multifunctional mobile devices, an appropriate combination of technology features, circuit-level low-power techniques, and system architecture is implemented in a GSM/Edge baseband processor with multimedia and mixed-signal extensions. Power reduction techniques and performance requirements are derived from an analysis of relevant use cases and applications. The 44 mm2 baseband processor is fabricated in a 90-nm low-power CMOS technology with triple-well option and dual-gate oxide core devices. The ARM926 core achieves a maximum clock frequency of 380 MHz at 1.4-V supply due to the usage of thin oxide (1.6 nm) devices. Power dissipation can be adapted to the performance requirements by means of combined voltage and frequency scaling to reduce active power consumption in medium-performance mode by 68%. To reduce leakage currents during standby mode, large SRAM blocks, nFET sleep transistors, and circuit components with relaxed performance requirements are implemented using devices with 2.2-nm gate oxide thickness
Keywords: 1.4 V; 2.2 nm; 380 MHz; 90 nm; ARM926 core; GSM/Edge multimedia-enhanced baseband processor; Dual-gate oxide core devices; Frequency scaling; Large SRAM blocks; Leakage currents; Low power CMOS technology; Mixed-signal extensions; Multifunctional mobile devices; Multimedia extensions; nFET sleep transistors; Standby mode; Triple-well option